2019
DOI: 10.1002/hfm.20810
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of custom‐made insoles and exercises on lower limb and back discomfort in assembly‐line workers in a rubber tire factory: A randomized controlled trial

Abstract: Many occupations require standing for prolonged periods, which can be a major contributor to musculoskeletal problems and cause disturbances in different parts of the body, especially the lower back and lower extremities. The aim of this study was to investigate the effect of custom‐made insoles and exercise training on the lower limb and lower back discomfort in workers on a production line at a rubber tire factory. One hundred male workers (mean age 35.96 years, work experience of 10.62 years, standing time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Other interventions to prevent musculoskeletal discomfort have used exercise and insoles in a work environment. An intervention of 8 weeks of simultaneous use of custom-made insoles and exercises might be an effective intervention to reduce discomfort in the lower limbs and lower back in workers who remain standing for prolonged periods [61].…”
Section: Discussionmentioning
confidence: 99%
“…Other interventions to prevent musculoskeletal discomfort have used exercise and insoles in a work environment. An intervention of 8 weeks of simultaneous use of custom-made insoles and exercises might be an effective intervention to reduce discomfort in the lower limbs and lower back in workers who remain standing for prolonged periods [61].…”
Section: Discussionmentioning
confidence: 99%
“…The foot morphology and characteristics of Taiwanese and Japanese individuals are different (Lee et al, 2015). Providing a proper insole for individual users can improve the feeling of discomfort (Mousavi et al, 2019; Niu et al, 2020). Thus, a redesign of the arch pad shape according to the anthropometric data and foot features of the target population is one of the possible ways to improve discomfort in the arch and midfoot area.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of interventions in the workplace have been proposed to reduce and prevent back pain in workers: sit-stand workstations [ 15 ], exercise [ 16 , 17 ], stretching [ 18 ], footrests [ 19 ], breaks [ 20 ], insoles for shoes [ 21 ], etc. However, no studies have been found that addressed assembly line workers with spine traction intervention in prolonged standing conditions.…”
Section: Introductionmentioning
confidence: 99%